The Meaning of Terms in The Bite Nggukale Wedding of The Tolaki Tribe in Konawe District - Ilham; Sulistyowati (Universitas Islam Negeri Palopo, 2025)
This study discusses the terms used in the traditional Bite Nggukale wedding ceremony in Konawe Regency. The purpose of this study is to describe the cultural meanings and explain the functions of the terms used in the traditional Bite Nggukale wedding ceremony. The research method used in this study is qualitative descriptive. In collecting data, the author used documentation and interviews. In the data analysis stage, the author used ethnosemantics to reveal the cultural meanings contained in the terms of the Bite Nggukale traditional wedding ceremony. Ethnolinguistics is the study of terms related to semantic meanings, such as kinship, color, flora, and fauna, to reveal cultural meanings. The results show that there are fifteen terms used in the traditional wedding ceremony of Bite Nggukale. The data includes the terms pabitara, toonomotuo, tolea, sara pombesanggarai, sara pomberahi, sara pombepende, kalosara, powokasi obiri, asolawa sawu lipa, obite tinongo nggukale, asondumbu okasa, oaso kiniku sara, and mowindahako. The cultural elements contained in these terms indicate kinship terms used in resolving traditional marriage processes.